Implementation of Hot Standby Router Protocol (HSRP) And Virtual Router Redundancy Protocol (VRRP) - Akhmad Fauzaan Azhar; Fatoni (Institute of Information Technology and Social Science (IITSS), 2025)
The rapid evolution of computer network technology mandates the provision of stable and efficient network services. A significant operational vulnerability arises when a primary router, responsible for network stabilization, operates without a redundant backup router to maintain continuity in the event of its failure. Consequently, this study proposes the addition of a Cisco router to mitigate potential operational constraints associated with the primary router. The backup router is configured to automatically assume the primary router's tasks upon the detection of an operational issue, thereby preserving network stability. The primary objective of this research is to implement the Hot Standby Router Protocol (HSRP) and the Virtual Router Redundancy Protocol (VRRP) to enhance network availability at the Palembang Office of the Personnel and Human Resources Development Agency (BKPSDM). The research methodology is based on Action Research, comprising five distinct phases: Diagnosing, Action Planning, Action Taking, Evaluating, and Learning. Data were collected through field observations, interviews, and a comprehensive literature review. The study involved deploying a redundant network solution utilizing HSRP and VRRP within the BKPSDM's network infrastructure. Quality of Service (QoS) performance was evaluated using standard network utilities, specifically ping and traceroute, to test the implemented HSRP and VRRP methods. The successful implementation of HSRP and VRRP is projected to result in a measurable improvement in network availability at the Palembang Office of the Personnel and Human Resources Development Agency compared to the previous configuration.